High-fidelity light-field display with enhanced information utilization by modulating chrominance and luminance separately - Zhaohe Zhang; Xunbo Yu; Xin Gao; Boyang Liu; Hanbo Wang; Chao Gao; Zeyu Hao; Ruiang Zhao; Xinzhu Sang (Light: Science & Applications)
Abstract Light-field displays typically consist of a two-dimensional (2D) display panel and a light modulation device. The 2D panel presents synthesized parallax images, with the total information content of the three-dimensional (3D) light field dictated by the panel’s total resolution. Angular resolution serves as a critical metric for light-field displays, where higher angular resolution correlates with a more realistic 3D visual experience. However, the improvement of angular resolution is typically accompanied by a reduction in spatial resolution, due to the limitations of the 2D display panel’s total resolution. To address this challenge, a light-field display method with enhanced information utilization is introduced, achieved through the independent modulation of chrominance and luminance. A static light-field image display system is proposed to verify the feasibility of this method. The system employs a bidirectional angular modulation grating (BAMG) and a collimated light source (CLS) to create uniformly distributed viewpoints in space. A luminance modulation film (LMF) and a chrominance modulation film (CMF) are utilized to modulate the light-field information, with chrominance and luminance synthesized images printed at pixel densities of 720 pixels per inch (PPI) and 8000 dots per inch (DPI), respectively, to align with the differential sensitivities of the human visual system. In the experiment, the proposed display system achieves a full-parallax, high-fidelity color display with a 98.2° horizontal and 97.7° vertical field of view (FOV). So, the light-field display method of modulating chrominance and luminance separately has been proven to achieve high-fidelity display effects.